AUTOMATIC DOOR SIMULATOR DESIGN BASED ON ARDUINO UNO USING PROTEUS SOFTWARE - Rindi Wulandari (Journal of Green Science and Technology, 2021)
In this pandemic era, doors in public places are one of the objects that can be an intermediary for the transmissionof the Covid-19 virus. That's why various kinds of developments in the field of technology are designed to provide an alternative in avoiding the transmission of the Covid-19 virus through doors in public places.The purpose of this study is to design an Arduino Uno-based automatic door simulator using Proteus software. The sensor used in this system is a PIR (Passive Infra Red) sensor. The way the system works is that when the PIR sensor detects someone's movement, the Data OUT Pin will be HIGH. Because this pin is connected to the Arduino, it will detect this HIGH Signal and detect that someone is approaching the door and will provide input to the DC motor, then the DC motor will move to the right or left to pull the door. From the simulation results, the delay between sensor readings and the movement of the DC motor is about 3 to 5 seconds.